The Changing Face of Veterinary Professionalism—Implications for Veterinary Education - Stuart Gordon; Tim Parkinson; Stacey Byers; Kerri Nigito; Adria Rodriguez; Catherine Werners-Butler; Jaelene Haynes; Talia Guttin (Education Sciences, 2023)
Veterinary professionals need to maintain currency with the rapidly expanding knowledge, techniques, and diagnostic skills available to the profession, while also accommodating the developing needs and expectations of clients and other veterinary stakeholders. Today, societal influence and expectations impose a heavy demand on veterinary practitioners, making it essential for tertiary veterinary education to equip veterinary graduates with the skills necessary to face these challenges and flourish in their profession. This paper explores four challenges faced by veterinary education in the development, maintenance, and upkeep of professional skills training: the divarication between employer expectations and veterinary education, the impact of demographic changes on the profession, the influence of institutional structures on the teaching of professionalism, and the risks associated with outdated models of professionalism training. The teaching of professionalism in veterinary education must continually evolve. One issue that may hinder this process is a divergence between the expectations of employers and tertiary institutions regarding the employability skills required by veterinary graduates. Veterinary professionalism education must also consider changing demographics within the profession and within society to provide all new graduates with the skills and tools necessary to succeed in the workplace, establish a sustainable work–life balance, combat burnout in new graduates, and be equipped to serve the general public. Failure to do this could result in professionalism teaching becoming complicit in a socialization process that perpetuates gender and cultural inequalities. This paper outlines some of the changes that have occurred in the veterinary profession and their implications on veterinary professionalism education. The article champions the necessity for veterinary professionalism education to evolve in concert with the constant changes in the profession.